When NAPHIRE shells maize gains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A new prototype maize sheller has been developed by the Philippine National Post-Harvest Institute for Research and Extension (NAPHIRE). It incurs lower shelling losses and less kernel damage than other shellers popularly used in the country. Its...